2019
DOI: 10.1186/s13601-019-0299-y
|View full text |Cite|
|
Sign up to set email alerts
|

Highlights and recent developments in skin allergy and related diseases in EAACI journals (2018)

Abstract: The European Academy of Allergy and Clinical Immunology (EAACI) supports three journals: Allergy, Paediatric Allergy and Immunology as well as Clinical and Translational Allergy. The major goals of EAACI include (i) supporting health promotion in which the prevention of allergy and asthma plays a critical role and (ii) disseminating the knowledge of allergy to all stakeholders including the EAACI junior members. Substantial progress was made in 2018 in the identification of basic mechanisms of atopic dermatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
(58 reference statements)
1
8
0
1
Order By: Relevance
“…154 Future studies are needed to explore links between AD and diet diversity, lifestyle, gene environment, microbial diversity, and allergy outcomes. 155,156 Microbial, epithelial, and immune interactions are fundamental to skin physiology. 157 Patients with AD reveal an imbalance of the microbiome, and toll-like receptor 2 plays an essential role in the recognition and defense against S. aureus.…”
Section: Epigenetic Regulation Of the Mucosal Barrier In Asthmamentioning
confidence: 99%
“…154 Future studies are needed to explore links between AD and diet diversity, lifestyle, gene environment, microbial diversity, and allergy outcomes. 155,156 Microbial, epithelial, and immune interactions are fundamental to skin physiology. 157 Patients with AD reveal an imbalance of the microbiome, and toll-like receptor 2 plays an essential role in the recognition and defense against S. aureus.…”
Section: Epigenetic Regulation Of the Mucosal Barrier In Asthmamentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the affiliation list. The first affiliation for M. Jutel was omitted.…”
Section: Correction To: Clin Transl Allergy (2019) 9:60 101186/s1360mentioning
confidence: 99%
“…The review article in Clinical Translational Allergy provides you with a summary of articles published in our journals related to skin allergy. 1 Allergy features a review on articles reporting on respiratory diseases, 2 and our journal summarizes the themes of food and drug allergy, as well as anaphylaxis. 3 With this common initiative, we hope to give our readership and the members of EAACI a glance at the very vivid scientific life in our field.…”
Section: Early Life Events Influence Asthma and Food Allergy And Howmentioning
confidence: 99%
“…It is a good time to look back at the last months with a summary of the latest and most prominent publications in the three European Academy of Allergy and Immunology (EAACI) journals. The review article in Clinical Translational Allergy provides you with a summary of articles published in our journals related to skin allergy . Allergy features a review on articles reporting on respiratory diseases, and our journal summarizes the themes of food and drug allergy, as well as anaphylaxis .…”
mentioning
confidence: 99%